2018
DOI: 10.1111/epi.14049
|View full text |Cite
|
Sign up to set email alerts
|

Standards for testing and clinical validation of seizure detection devices

Abstract: To increase the quality of studies on seizure detection devices, we propose standards for testing and clinical validation of such devices. We identified 4 key features that are important for studies on seizure detection devices: subjects, recordings, data analysis and alarms, and reference standard. For each of these features, we list the specific aspects that need to be addressed in the studies, and depending on these, studies are classified into 5 phases (0-4). We propose a set of outcome measures that need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
127
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 21 publications
1
127
0
5
Order By: Relevance
“…Several studies have shown that intracranial electrodes, if positioned correctly in relation to the seizure focus, can be used to detect more seizures than scalp EEG electrodes. 34 Such standards should guide future studies on novel seizure-detection devices to facilitate comparison between studies and meta-analyses. 33 Another way to get around this problem is to perform large-scale trials comparing clinical outcomes for groups of patients in whom decision-making was based on traditional methods to other groups in whom decision-making was informed by whatever method in question.…”
Section: Limitationsmentioning
confidence: 99%
“…Several studies have shown that intracranial electrodes, if positioned correctly in relation to the seizure focus, can be used to detect more seizures than scalp EEG electrodes. 34 Such standards should guide future studies on novel seizure-detection devices to facilitate comparison between studies and meta-analyses. 33 Another way to get around this problem is to perform large-scale trials comparing clinical outcomes for groups of patients in whom decision-making was based on traditional methods to other groups in whom decision-making was informed by whatever method in question.…”
Section: Limitationsmentioning
confidence: 99%
“…There is a well‐documented need for wearable seizure detection devices and a marked increase in the number of papers reporting such attempts . However, more validation studies are needed to provide proof of utility and accuracy of these tools . Only very few multicenter, prospective, blinded phase 3 studies have provided compelling evidence of effective real‐time seizure detection .…”
Section: Introductionmentioning
confidence: 99%
“…However, more validation studies are needed to provide proof of utility and accuracy of these tools . Only very few multicenter, prospective, blinded phase 3 studies have provided compelling evidence of effective real‐time seizure detection . These studies are typically conducted in epilepsy monitoring units (EMUs), which differ from the natural home environment, in particular regarding patients’ mobility .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another phase‐2 study that retrospectively analyzed EMG signals recorded with conventional amplifiers in EMU, reported a different approach . The algorithm used Hotelling's T‐squared power analysis of compound muscle action potentials, and it was patient‐tailored: MVC was initially measured in each patient to establish the baseline (physiologic) threshold .…”
Section: Emg‐based Automated Detection Of Convulsive Seizuresmentioning
confidence: 99%